Radical prostatectomy versus external beam radiotherapy with androgen deprivation therapy for high-risk prostate cancer: a systematic review - Berdine L. Heesterman; Katja K. H. Aben; Igle Jan de Jong; Floris J. Pos; Olga L. van der Hel (BMC Cancer, 2023)
Abstract Background To summarize recent evidence in terms of health-related quality of life (HRQoL), functional and oncological outcomes following radical prostatectomy (RP) compared to external beam radiotherapy (EBRT) and androgen deprivation therapy (ADT) for high-risk prostate cancer (PCa). Methods We searched Medline, Embase, Cochrane Database of Systematic Reviews, Cochrane Controlled Trial Register and the International Standard Randomized Controlled Trial Number registry on 29 march 2021. Comparative studies, published since 2016, that reported on treatment with RP versus dose-escalated EBRT and ADT for high-risk non-metastatic PCa were included. The Newcastle–Ottawa Scale was used to appraise quality and risk of bias. A qualitative synthesis was performed. Results Nineteen studies, all non-randomized, met the inclusion criteria. Risk of bias assessment indicated low (n = 14) to moderate/high (n = 5) risk of bias. Only three studies reported functional outcomes and/or HRQoL using different measurement instruments and methods. A clinically meaningful difference in HRQoL was not observed. All studies reported oncological outcomes and survival was generally good (5-year survival rates > 90%). In the majority of studies, a statistically significant difference between both treatment groups was not observed, or only differences in biochemical recurrence-free survival were reported. Conclusions Evidence clearly demonstrating superiority in terms of oncological outcomes of either RP or EBRT combined with ADT is lacking. Studies reporting functional outcomes and HRQoL are very scarce and the magnitude of the effect of RP versus dose-escalated EBRT with ADT on HRQoL and functional outcomes remains largely unknown.